Reestablishment of Redox Homeostasis in the Nociceptive Primary Afferent as a Mechanism of Antinociception Promoted by Mesenchymal Stem/Stromal Cells in Oxaliplatin-Induced Chronic Peripheral Neuropathy - Anna Lethicia L. Oliveira; Gisele G. L. Santos; Renan F. Espirito-Santo; Gessica Sabrina A. Silva; Afrânio F. Evangelista; Daniela N. Silva; Milena B. P. Soares; Cristiane Flora Villarreal (Stem Cells International)
Painful neuropathy is a common adverse effect of oxaliplatin (OXL), a platinum-derivative chemotherapeutic agent. Oxidative stress and mitochondrial dysfunction are key factors contributing to the development of OXL-induced peripheral neuropathy (OIPN). Based on the antioxidant and antinociceptive properties of mesenchymal stem/stromal cells (MSC), the present study tested the hypothesis that MSC induce antinociceptive effects during OIPN by promoting regulation of redox environment and mitochondrial homeostasis in the nociceptive primary afferents. C57Bl/6 mice submitted to the OXL-chronic neuropathy induction protocol by repeated intravenous administration of OXL (1 mg/kg) were evaluated to determine the paw mechanical and thermal nociceptive thresholds using the von Frey filaments and cold plate tests, respectively. Two weeks after the neuropathy induction, mice were treated with bone marrow-derived MSC (1×106), vehicle, or gabapentin (GBP, 70 mg/kg). Four weeks later, mitochondrial morphology, gene expression profile, and oxidative stress markers in the sciatic nerve and dorsal root ganglia (DRG) were evaluated by transmission electron microscopy, RT-qPCR, and biochemical assays, respectively. OXL-treated mice presented behavioral signs of sensory neuropathy, such as mechanical allodynia and thermal hyperalgesia. The behavioral painful neuropathy was completely reverted by a single administration of MSC, while the daily treatment with GBP induced only a short-lived antinociceptive effect. The ultrastructural analysis of the sciatic nerve and DRG of OIPN mice revealed a high proportion of atypical mitochondria in both myelinated and unmyelinated fibers. Importantly, this mitochondrial atypia was strongly reduced in MSC-treated neuropathic mice. Moreover, MSC-treated neuropathic mice showed upregulation of Sod and Nrf2 mRNA in the sciatic nerve and DRG. In line with this result, MSC reduced markers of nitrosative stress and lipid peroxidation in the sciatic nerve and DRG from OIPN mice. Our data suggest that the reestablishment of redox homeostasis in the nociceptive primary afferents is a mechanism by which MSC transplantation reverts the OXL-induced chronic painful neuropathy.